Da’wah and the Social Movement of Chinese Muslim in Indonesia - Wahyudi, Winarto Eka; Zuhri, Achmad Muhibin (Journal of Integrative International Relations, 2019)
This article aims to discuss Chinese Muslim social movements which are packed with da'wah activities. In Indonesia, in the last decades, this community has become a separate social phenomenon. This study used a qualitative-phenomenological method and will answer important questions. Do Chinese Muslims use social movements as a strategy to overcome their existential problems? And why does this community intensively carry out social roles as their da'wah packaging? In the end, this study found a positive relationship between da'wah and social movements as one of the efforts of Chinese Muslims to disseminate Islamic teachings in accordance with their socio-cultural character on the one hand. And through the social role, the Chinese Muslims intend to socialize to the public that there are also ethnic Chinese who embrace Islam on the other hand.